The Future of MK Legal Instruments In Mapping The Study of The Philosophy of Utilitarianism Jeremy Bentham - Shalihah, Aini; Khoyyinah, Khoyyinah (Al-Daulah: Jurnal Hukum dan Perundangan Islam, 2023)
This research analyzes the changes to the Constitutional Court Law in Indonesia, focusing on their socio-political consequences. The research method used is a normative legal methodology, which evaluates the socio-political impact of the changes based on Jeremy Bentham’s theory of utilitarianism. The research considers factors such as the organization and the role of the Constitutional Court, the independence of judges, and the state of democracy in Indonesia. The study shows that the Constitutional Court Law changes have significantly impacted societal welfare, with some parties supporting increased constitutional protection and human rights. In contrast, others are concerned about the potential politicization and reduced effect reduced effectiveness of other democratic institutions. The practical implication of this research is to provide policy recommendations to improve the regulation and implementation of the Constitutional Court in Indonesia to maximize overall public welfare. Keywords: Constitutional Court, Utilitarianism, social welfare.